Sustainable development path research on urban transportation based on synergistic and cost-effective analysis: A case of Guangzhou. (August 2021) - Jiao, Jiandong; Huang, Ying; Liao, Cuiping; Zhao, Daiqing
Highlights: The CO2 and air pollutants emissions of entire urban transportation are calculated. The synergies and cost-effectiveness of 21 measures are quantitatively analyzed. Adjusting and regulating measures have significant synergies and cost-effectiveness. Energy substitution measures have good synergies, but poor cost-effectiveness. Promoting LNG measures have good cost-effectiveness, but poor synergies. Abstract: Urban transportation plays an important role in slowing down global warming and controlling environmental pollution. To explore the sustainable development paths of Guangzhou transportation, the synergies and cost-effectiveness of emission mitigations on CO2 and air pollutants are quantitatively evaluated under different control measures in this paper. The radar chart analysis method, marginal abatement cost curves, and emission mitigation effect normalization are used to identify and evaluate the synergies and cost-effectiveness. The results show that the control measures to adjust transport modes and regulate private cars can achieve significant synergies and cost-effectiveness of emission mitigations on CO2 and air pollutants, and should be implemented as a high priority. In contrast, the control measures to promote the application of electricity, hydrogen energy, and bio-fuel have effective synergies, but with high costs, and should be implemented as a lower priority. Moreover, the control measures to popularize Liquefied Natural Gas (LNG) have good cost-effectiveness, but with poor synergies due to the emission increments of HC and CO. Unless HC and CO emissions can be effectively reduced through the installation of terminal removal devices for air pollutants, the implementation of the control measures related to LNG will remain a low priority.